URGENSI SINKRONISASI AKAD PERBANKAN SYARIAH DENGAN AKAD JAMINAN HARTA BENDA MENURUT PRINSIP SYARIAH - Nurfadillah, Nurfadillah (Jurnal Kajian Hukum Islam, 2019)
In accordance with the needs and principles of benefits and goods, muamalah agreements based on sharia principles have been politicized into national law with the enactment of the Law on Sharia Banking. The law has clearly set out about sharia banking activities and procedures for resolving disputes. However, it does not regulate the guarantee law according to sharia principles. From the results of the study, it can be concluded that the collateral position in the muamalah contract must be trustworthy so that no collateral is needed. But in practice Islamic banks often require collateral for property as a condition for financing. This is also confirmed by the National Sharia Board which allows financing with assets (rahn). Because there is no arrangement of guarantee contracts based on sharia principles, the binding of the collateral is carried out using national guarantee law, which is not a guarantee contract based on sharia principles. So that synchronization is needed between muamalah contract and rahn guarantee contract